High Performance Photoinitiating Systems for Holography Recording: Need for a Full Control of Primary Processes. Issue 46 (26th September 2014) - Ibrahim, Ahmad; Allonas, Xavier; Ley, Christian; Kawamura, Koichi; Berneth, Horst; Bruder, Friedrich‐Karl; Fäcke, Thomas; Hagen, Rainer; Hönel, Dennis; Rölle, Thomas; Walze, Guenther; Weiser, Marc Stephan
Abstract Optimization of holography recording in photopolymers was studied from the point of view of a quite general process, that is, the photogeneration of radicals. On the basis of a dye/coinitiator photoinitiating system, the effect of primary events and their relative efficiency was investigated with respect to the final overall properties, such as the diffraction efficiency. Quenching of the dye excited states by the borate salts coinitiators exhibits important differences depending on the dye used (Rose Bengal or Safranine O). Keeping in mind that both singlet and triplet states of the dyes can react, and taking into account the viscosity of the matrix, a method to evaluate the overall quantum yield of radicals released is proposed. It is found that this quantum yield well correlates with the maximum rate of photopolymerization. More interestingly, the dose required to obtain a given diffraction efficiency was found to be also governed by the radical quantum yield, showing that the final property is directly governed by primary events. This shed some light on the efficiency of photochemical pathway to generate radicals for use in organic or polymer areas.